AMANAH IN INVENTORY MANAGEMENT FOR FOOD WASTE REDUCTION IN CULINARY MSMEs - Andi Rezky Nur Aziza; Nurlisa Safitri; Muhammad Fakhri Amir (Program Studi Hukum Ekonomi Syariah, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
This study examines the role of the Islamic ethical value of amānah in controlling food waste as a preventive measure against tabdzir through inventory management practices at Café Teras, a local culinary business in Bone Regency. From the perspective of Islamic Economic Law, food waste is not merely regarded as operational inefficiency but is also understood as a form of resource misuse that is explicitly discouraged. The research aims to analyze how the integration of amānah with contemporary inventory management principles functions as an operational mechanism to reduce food waste while maintaining compliance with Sharīʿah principles. This study employs a qualitative field research approach, utilizing in-depth interviews and direct observations involving the owner, cashier, and kitchen and bar staff. The findings indicate that the internalization of amānah fosters discipline, carefulness, and accountability in inventory control, thereby strengthening the implementation of FIFO, daily procurement of perishable ingredients, and the contextual adaptation of EOQ and JIT models in response to limited business capital. The study concludes that inventory management grounded in the value of amānah not only enhances operational efficiency but also serves as an effective instrument for preventing tabdzir within culinary business practices based on Islamic Economic Law. Abstrak Penelitian ini mengkaji peran nilai etika Islam berupa amānah dalam pengendalian food waste sebagai upaya pencegahan praktik tabdzir melalui manajemen persediaan di Café Teras, sebuah usaha kuliner lokal di Kabupaten Bone. Dalam perspektif Hukum Ekonomi syariah, food waste tidak hanya dipandang sebagai inefisiensi operasional, tetapi juga sebagai bentuk pemborosan sumber daya yang dilarang. Penelitian ini bertujuan menganalisis bagaimana integrasi nilai amānah dengan prinsip manajemen persediaan modern berfungsi sebagai mekanisme operasional untuk menekan food waste sekaligus menjaga kepatuhan terhadap prinsip syariah. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan penelitian lapangan melalui wawancara mendalam dan observasi terhadap pemilik, kasir, serta staf dapur dan bar. Hasil penelitian menunjukkan bahwa internalisasi nilai amānah mendorong disiplin, ketelitian, dan akuntabilitas dalam pengelolaan persediaan, serta memperkuat penerapan FIFO, pembelian harian bahan perishable, dan adaptasi EOQ serta JIT sesuai keterbatasan modal usaha. Penelitian ini menyimpulkan bahwa manajemen persediaan berbasis nilai amānah tidak hanya meningkatkan efisiensi operasional, tetapi juga berfungsi sebagai instrumen pencegahan tabdzir dalam praktik usaha kuliner berbasis Hukum Ekonomi syariah.